2022
DOI: 10.3389/fcimb.2022.879423
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Effect of Coaggregation Between Fusobacterium nucleatum and Streptococcus gordonii on the Synergistic Virulence to Human Gingival Epithelial Cells

Abstract: In subgingival plaque biofilms, Fusobacterium nucleatum is closely related to the occurrence and development of periodontitis. Streptococcus gordonii, as an accessory pathogen, can coaggregate with periodontal pathogens, facilitating the subgingival colonization of periodontal pathogens. Studies have shown that F. nucleatum can coaggregate with S. gordonii and colonize the subgingival plaque. However, most studies have focused on monocultures or coinfection of species and the potential impact of coaggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Our previous study reported that the pro-inflammatory factors IL-1β and IL-6 secreted by macrophages were markedly reduced following the coaggregated S. gordonii and Fnp infection (Liu et al 2021 ). Another article of our group found that compared with coculture of species, the coaggregated S. gordonii and Fnp enhanced proinflammatory cytokines TNF-α and IL-6 production by human gingival epithelial cells (hGECs) (Yang et al 2022 ). These results also suggested that the immunoregulatory properties of interspecies interaction might be host cell-specific, since coaggregation between S. gordonii and Fnp exerted pro-inflammatory effects on HGECs but anti-inflammatory roles on macrophages (Liu et al 2021 ; Yang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study reported that the pro-inflammatory factors IL-1β and IL-6 secreted by macrophages were markedly reduced following the coaggregated S. gordonii and Fnp infection (Liu et al 2021 ). Another article of our group found that compared with coculture of species, the coaggregated S. gordonii and Fnp enhanced proinflammatory cytokines TNF-α and IL-6 production by human gingival epithelial cells (hGECs) (Yang et al 2022 ). These results also suggested that the immunoregulatory properties of interspecies interaction might be host cell-specific, since coaggregation between S. gordonii and Fnp exerted pro-inflammatory effects on HGECs but anti-inflammatory roles on macrophages (Liu et al 2021 ; Yang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another article of our group found that compared with coculture of species, the coaggregated S. gordonii and Fnp enhanced proinflammatory cytokines TNF-α and IL-6 production by human gingival epithelial cells (hGECs) (Yang et al 2022 ). These results also suggested that the immunoregulatory properties of interspecies interaction might be host cell-specific, since coaggregation between S. gordonii and Fnp exerted pro-inflammatory effects on HGECs but anti-inflammatory roles on macrophages (Liu et al 2021 ; Yang et al 2022 ). In this study, the coaggregation of Ef and Fnp dramatically decreased the levels of pro-inflammatory cytokines IL-6, TNF-α, and chemokine MCP-1 secreted by macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,42 S. gordonii can also co-aggregate with F. nucleatum, facilitating its colonization in the subgingival plaque and aggravating the inflammatory response of human gingival epithelial cells. 43 Fig. 3a shows the agar plate images of P. gingivalis, F. nucleatum and S. gordonii.…”
Section: In Vitro Antibacterial Efficacymentioning
confidence: 99%
“… 1 Streptococcus gordonii ( S. gordonii ) is an early colonizer that can easily attach to the tooth surfaces and facilitate the colonization of other periodontal pathogens to establish subgingival biofilms. 2 , 3 Fusobacterium nucleatum ( F. nucleatum ) can act as a bridge pathogen between the early and late colonizers by creating favorable conditions for the outgrowth of the late colonizer, such as Porphyromonas gingivalis ( P. gingivalis ), which is a keystone pathogen in the etiology of chronic periodontitis. 4 P. gingivalis can invade cells and tissues where they can maintain viability to avoid immune surveillance, thus easily developing antibiotic resistance and producing persistent infection.…”
Section: Introductionmentioning
confidence: 99%